Transcriptional induction of the IMD signaling pathway and associated antibacterial activity in the digestive tract of cat fleas (Ctenocephalides felis) - Katie Weber; Dhruva Karnik; Lisa D. Brown (Parasites & Vectors)
Abstract Background Fleas are insect vectors that transmit several Gram-negative bacterial pathogens acquired by ingesting infected vertebrate blood. To combat foodborne illness, insect midgut epithelial cells are armed with efficient microbial recognition and control systems, such as the immune deficiency (IMD) pathway that regulates the expression of antimicrobial peptides (AMPs). However, despite their medical and veterinary importance, relatively little is known about the IMD signaling pathway and production of AMPs in the digestive tract of cat fleas (Ctenocephalides felis). Methods In the present study, we measured the expression of target genes comprising the IMD pathway, as well as corresponding AMP transcripts, in the digestive tract of C. felis following exposure to three different species of bacteria: Gram-negative Bartonella henselae (a flea-borne pathogen), Gram-negative Serratia marcescens (a model laboratory species), and Gram-positive Micrococcus luteus (a model laboratory species). Additionally, we examined the antibacterial activity of proteins isolated from the flea digestive tract in vitro following bacterial challenge and at different days post adult emergence to determine if feeding-induced antibacterial activity varies with age. Results In our analysis of C. felis, we observed an increase in the expression of representative IMD pathway genes and associated AMP transcripts, indicating the activation of the IMD pathway. Furthermore, our results revealed that different bacterial species elicit distinct transcriptional profiles of IMD pathway genes, suggesting a species-specific response to bacterial invasion. We found that the gut of C. felis produces antibacterial molecules as a localized defense mechanism. Additionally, we observed that proteins with antimicrobial properties are synthesized as part of local defense mechanisms in the gut, with differential patterns of antibacterial activity related to infection status and age. Conclusions Our findings provide essential insights into the potential mechanisms by which cat fleas regulate immune responses in their digestive tract against different bacterial species. Graphical Abstract